2007
DOI: 10.1264/jsme2.22.32
|View full text |Cite
|
Sign up to set email alerts
|

Interference Expression at Levels of the Transcript and Protein among Group 1, 2, and 3 Sigma Factor Genes in a Cyanobacterium

Abstract: The sigma (σ) factor is a subunit for the RNA polymerase (RNAP) holoenzyme and can confer promoter selectivity at a target gene. On the inactivation of all group 2 and 3 σ factor genes, expression at the level of the transcript and protein was examined under continuous white light at an exponential phase in a unicellular cyanobacterium, Synechocystis sp. strain PCC 6803. It was found that interference expression exists among group 1, 2, and 3 σ factor genes. Authentic echoes of the expression did not always re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…For example, the work of Lemeille et al (25) included nitrogen deprivation and long-term growth as experimental conditions, and they suggested a network of transcriptional interactions between the group 2 factors. The recent work of Matsui et al (27) indicated that the group 3 sigma factors may play a role in these interactions. Importantly, Imamura et al (19) purified all group 1 and group 2 factors and determined their intracellular levels under steadystate growth conditions, as well as their growth-phase-dependent changes.…”
mentioning
confidence: 99%
“…For example, the work of Lemeille et al (25) included nitrogen deprivation and long-term growth as experimental conditions, and they suggested a network of transcriptional interactions between the group 2 factors. The recent work of Matsui et al (27) indicated that the group 3 sigma factors may play a role in these interactions. Importantly, Imamura et al (19) purified all group 1 and group 2 factors and determined their intracellular levels under steadystate growth conditions, as well as their growth-phase-dependent changes.…”
mentioning
confidence: 99%
“…Complicated crosstalk regulation has been reported between sigma factors and suggested to be an important adaptation to different environmental and physiological conditions (Lemeille et al, 2005a, b). Interference with expression at the RNA and protein level was observed among group 1, 2 and 3 sigma factors (Matsui et al, 2007). Moreover, sigma factors can be downstream targets of histidine kinase, while differential expression of histidine kinase has also been reported in sigma-factor-disrupted mutants (Murata & Los, 2006;Summerfield & Sherman, 2007).…”
Section: Mechanisms Of Slr0643 In Acid Acclimationmentioning
confidence: 96%
“…At pH 7.5, disruption of slr0643 caused upregulation of sigB, sigC and sigD and downregulation of sigF and sigH (Table 3). Autoregulation has been reported for sigF and sigH expression (Asayama & Imamura, 2008;Matsui et al, 2007), thus rendering anti-Sigma factors of SigF and SigH the possible target of Slr0643. However, at pH 6.5, transcript abundance of sigF was similar in the mutant and wild-type, hence it was excluded from being directly downstream of Slr0643 (Table 3).…”
Section: Mechanisms Of Slr0643 In Acid Acclimationmentioning
confidence: 99%
“…For the reverse transcribed-PCR analysis, cells in a logarithmic growth phase were harvested, total RNA was isolated from M. aeruginosa B-35 and K-139 using hot phenol, and cDNA was prepared as described previously [8]. The reverse transcribed reaction was performed as described [15]. The primers sets for the mcnA and mcnD genes were F-mcnA-RT (5'-CGCCCAAAAATGTCACC-3') and R-mcnA (5'-AAGGGGAAATCTTGGGC-3') based on the mcnA K-139 gene (accession number, AB481215) and F-hal-RT (5'-GGCGAATCAATCTTTACATCG-3') and R-hal-RT (5'-TCACTTACCAATTGCCTC-3') based on the mcnD B-35 gene (AB481216), respectively.…”
mentioning
confidence: 99%